GANGGUAN BAGI SISWA SELAMA PEMBELAJARAN ONLINE - Riza Pahlevi, Mohammad (Nusantara Hasana Journal, 2022)
Internet Mediated Communication (IMC) emerged as a phenomenon where internet users are disturbed by the disturbances that arise. This study aims to understand the disturbances faced by students when interacting with and carrying out their studies using the internet during the pandemic. The results show that students access too much information that is not relevant to what they need because of the clicking reflex process. But the students still enjoy all the distractions and don't realize that they are running out of time to do their activities. It's just discovered recently that the disorder occurs due to the limited ability of the human brain to accept too much of the available information.